User study results on attitude perception of a mobile robot - Corujeira, J. (2018)
Teleoperating a mobile robot over rough terrain is difficult with current interaction implementations. These implementations compromise the human operators» situation awareness acquisition of the mobile robot»s attitude, which is crucial to maintain a safe teleoperation. So, we developed a novel haptic device, to relay a mobile robot»s attitude (roll and pitch) to the human operator. A user experiment was performed to evaluate the efficacy of this device in two configurations. A natural attitude configuration between the robot and haptic device, and an ergonomic attitude configuration, which shifts the representation of pitch to the yaw axis. Our results indicate participants were able to successfully perceive the attitude state in both configurations, the natural 58.79% and the ergonomic 63.18% of the times, both are significantly above the 1/3 probability chance. Interestingly, the perception of attitude state was significantly higher in the roll axis over the pitch axis, for the critical and unstable states.